Z dziejów kształtowania idei wychowania przedszkolnego na ziemiach polskich - Loyola-Opiela, Maria (Acta Universitatis Nicolai Copernici Pedagogika, 2015)
From the history of the idea of pre-primary education in the Polish lands The fusion of both the national idea and a religious revival with social work in the nineteenth century led to the search for indigenous solutions in the field of education. Because of attributable in the 2014 200th anniversary of the birth of cooperating with each other great personalities of this period: Edmund Bojanowski (1814–1871), August Cieszkowski (1814–1894) John Koźmian (1814–1877) and Peter Semenenko (1814–1886) should be reco gnize their contribution to the development of the foundations of native theory and practice of early education in the concept of rural nurseries. He combined their sincere enthusiasm and belief in the rightness of work for the revival of moral-religious and social nation through education of new generations. The richness of the diversity of their personalities, interests professions and personal opportunities led to the creation of the work in which the synergy of theory and practice has resulted in a coherent and dynamic system of early education as the first link of education. It assured a permanent basis for the functional and structural dimension of the system and meeting personal and material ensuring a clear identity and openness to the necessary changes due to the specific needs of people and the environment. This contribution and dimensions of the concept of rural nurseries are shown in this article.